2017
DOI: 10.3390/ijms18010097
|View full text |Cite
|
Sign up to set email alerts
|

RAB10 Interacts with the Male Germ Cell-Specific GTPase-Activating Protein during Mammalian Spermiogenesis

Abstract: According to recent estimates, 2%–15% of couples are sterile, and approximately half of the infertility cases are attributed to male reproductive factors. However, the reasons remain undefined in approximately 25% of male infertility cases, and most infertility cases exhibit spermatogenic defects. Numerous genes involved in spermatogenesis still remain unknown. We previously identified Male Germ Cells Rab GTPase-Activating Proteins (MGCRABGAPs) through cDNA microarray analysis of human testicular tissues with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…In our previous study, we found that TBC1D21 are localized to the peri-acrosomal and manchette regions in elongated spermatids and to the tail in mature sperms [31,32]. However, sperm-head defects have not been detected in Tbc1d21 -/sperm; moreover, the morphology of the sperm revealed the severe defects in the mitochondria and the axoneme (Figs 3 and 4).…”
Section: The Possible Cellular Roles Of Tbc1d21 In Intra-manchette Trmentioning
confidence: 82%
See 3 more Smart Citations
“…In our previous study, we found that TBC1D21 are localized to the peri-acrosomal and manchette regions in elongated spermatids and to the tail in mature sperms [31,32]. However, sperm-head defects have not been detected in Tbc1d21 -/sperm; moreover, the morphology of the sperm revealed the severe defects in the mitochondria and the axoneme (Figs 3 and 4).…”
Section: The Possible Cellular Roles Of Tbc1d21 In Intra-manchette Trmentioning
confidence: 82%
“…Grey lines indicate the possible interaction between two interactors via the STRING software. Red lines present the interactions demonstrated through co-IP in our previous studies[31,32,47].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…RAB3 and RAB27 are present in the acrosomal membrane and are essential for acrosomal exocytosis [97]. RAB27b was detected in the manchette of human and monkey spermatids [98], while RAB10 localizes to the manchette of mouse spermatids [99]. Moreover, RABL2 is essential for sperm tail function and male fertility and RAB8B is known to assist in junction dynamics of the testis [100].…”
Section: Small Gtpases (The Rab Family)mentioning
confidence: 99%